2022
DOI: 10.7717/peerj.13373
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of sensory sensitivity in women suffering from depression using transcutaneous electrical nerve stimulation

Abstract: Background Perception is the process or result of the process arising from the mental interpretation of the phenomena occurring, therefore it depends not only on physiology, but is also psychologically and socially conditioned. The aim of this study was to assess if there is a difference in the sensory sensitivity to an electrical stimulus in women suffering from depression and what the hedonic rating is of the lived experience of transcutaneous electrical nerve stimulation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Gibson et al in their study found that TENS also helped in relieving neuropathic pain, while Witkoś et al found that application of TENS relaxed the muscles and therefore, even helped in reducing anxiety and depression in such patients. Witkos et al in their study stated that the length of depression had no effect on the current-induced stimulus [ 14 , 15 ]. The study's purpose was to investigate and assess the effects of MFR and high-frequency TENS in participants with trapezius myalgia.…”
Section: Discussionmentioning
confidence: 99%
“…Gibson et al in their study found that TENS also helped in relieving neuropathic pain, while Witkoś et al found that application of TENS relaxed the muscles and therefore, even helped in reducing anxiety and depression in such patients. Witkos et al in their study stated that the length of depression had no effect on the current-induced stimulus [ 14 , 15 ]. The study's purpose was to investigate and assess the effects of MFR and high-frequency TENS in participants with trapezius myalgia.…”
Section: Discussionmentioning
confidence: 99%
“…The perception of pain, especially in response to electrical stimulation, is highly subjective and can be influenced by several physiological and psychological factors. 6,7 In women, these factors are further compounded by hormonal variations, skin characteristics, and differences in body composition. Studies have shown that hormonal fluctuations can affect pain perception and tolerance.…”
Section: Introductionmentioning
confidence: 99%